Randomized phase III trial of adjuvant chemotherapy with S-1 after curative treatment in patients with squamous-cell carcinoma of the head and neck (ACTS-HNC). - Kiyoaki Tsukahara; Akira Kubota; Yasuhisa Hasegawa; Hideki Takemura; Tomonori Terada; Takahide Taguchi; Kunihiko Nagahara; Hiroaki Nakatani; Kunitoshi Yoshino; Yuichiro Higaki; Shigemichi Iwae; Takeshi Beppu; et al. (PLoS ONE, 2015)
BACKGROUND:We conducted a phase III study to evaluate S-1 as compared with UFT as control in patients after curative therapy for stage III, IVA, or IVB squamous-cell carcinoma of the head and neck (SCCHN). PATIENTS AND METHODS:Patients were randomly assigned to the UFT group (300 or 400 mg day-1 for 1 year) or the S-1 group (80, 100, or 120 mg day-1 for 1 year). The primary end point was disease-free survival (DFS). Secondary end points were relapse-free survival, overall survival (OS), and safety. RESULTS:A total of 526 patients were enrolled, and 505 were eligible for analysis. The 3-year DFS rate was 60.0% in the UFT group and 64.1% in the S-1 group (HR, 0.87; 95%CI, 0.66-1.16; p = 0.34). The 3-year OS rate was 75.8% and 82.9%, respectively (HR, 0.64; 95% CI, 0.44-0.94; p = 0.022). Among grade 3 or higher adverse events, the incidences of leukopenia (5.2%), neutropenia (3.6%), thrombocytopenia (2.0%), and mucositis/stomatitis (2.4%) were significantly higher in the S-1 group. CONCLUSIONS:Although DFS did not differ significantly between the groups, OS was significantly better in the S-1 group than in the UFT group. S-1 is considered a treatment option after curative therapy for stage III, IVA, IVB SCCHN. TRIAL REGISTRATION:ClinicalTrials.gov NCT00336947 http://clinicaltrials.gov/show/NCT00336947.